Influencing Factors of Behavior Intention of Master of Arts Students Towards Online Education in Chengdu Public Universities, China - Min, Ying; Yang, Ming; Huang, Jingying; Duangekanong, Somsit (Scholar: Human Sciences, 2023)
Purpose: This study aims to investigate influencing factors of behavioral intentions to use online education of Master of Arts students from three public universities in the Chengdu region of China. The conceptual model contains perceived ease of use, perceived usefulness, social influence, effort expectancy, self-efficacy, perceived satisfaction, and behavioral intention. Research design, data and methodology: The researchers employed a quantitative approach of survey distribution to 501 participants. The sample techniques involve judgmental, quota and convenience sampling. The content validity method of Item Objective Congruence (IOC) Index was used, resulting all measuring items reserved by three experts. Pilot testing of 30 participants was approved under Cronbach’s Alpha reliability test. Confirmatory Factor Analysis (CFA) and Structural Equation Model (SEM) were performed for data analysis, including goodness of model fits, validity, and reliability testing. Results: Perceived ease of use had the strongest influence on perceived usefulness toward behavioral intention. Furthermore, perceived usefulness, social influence, self-efficacy, perceived satisfaction, except effort expectancy, significantly impacted behavioral intention. Conclusions: The findings lead to the recommendations that educational administrators at public universities to enhance the behavioral intention to use online education by providing well-design online learning system and promote various benefits of using.